PERANAN INSTITUSI PENDIDIKAN TEKNIKAL DALAM PEMUPUKAN KEMAHIRAN ‘EMPLOYABILITY’ PELAJAR (Sains Humanika, 2009)
Employability skill is the important skill that employers require from technical graduates in order to be employed. But not all technical graduates acquired the employability skill which meet the employers need. This paper is a concept paper which outlines the important aspects of employability skills, the roles and responsibility of technical institution to inculcate employability skills of an individual. Through this concept paper, some important employability skills aspects and method one suggest to inculcate the employability aspects. The literature review, reveals issues regarding employability skills amongst technical students and also the employability skills that employers require. A conceptual framework has been developed as a guideline for the tehnical institution and instructors, showing the interrelationship and networking between technical institute and industry in the process of inculcating the employability skills. Starategies and method of inculcating employability skill in the classroom has also been drawn out from this study. Overall study shows that technical institution must initiates in inculcating the employability skills of their students because employability skills has now become one of the most important skills besides technical skills in the industrial sector.
Keywords: Employability skill; technical skill; inculcate; institution and industry relationship; technical graduates